Predictive Maintenance: Monitoring Tools and Equipment - Au-Yong, C.P.; Ali, A.S.; Ahmad, F. (Royal Institution of Surveyors Malaysia, 2014)
Due to low service quality of maintenance management, high maintenance cost becomes a common issue in building industry of Malaysia. Lack of preventive measure is the problem that resulting poor maintenance performance. So, condition-based maintenance is introduced to improve the maintenance performance. Monitoring tools and equipment is seen as an important factor to ensure the efficiency of condition-based maintenance. So, this paper aims to determine the aspects of monitoring tools and equipment to be concerned in building maintenance, as well as to establish the relationship between the aspects and maintenance cost performance. A quantitative approach is adopted and performed through questionnaire survey. Furthermore, descriptive analysis and correlation analysis are used to analyse the research data. The literature review determines three aspects of monitoring tools and equipment to be considered in maintenance management. Furthermore, the research result demonstrates that the budget allocation for acquisition of monitoring tools and equipment, capability to operate the tools and equipment, as well as availability of the tools and equipment are significantly correlated to the maintenance cost variance. The research recommends the maintenance management to convince the clients or organisation to acquire advanced monitoring tools and equipment for implementation of condition-based maintenance. Besides that, provision of training is encouraged to ensure that the maintenance personnel are able to utilise the tools and equipment.